The Decline of Small Cities: Increased Competition from External Shopping Malls or Long-Term Negative Trends? - Sven-Olov Daunfeldt; Oana Mihaescu; Niklas Rudholm (Institute of Retail Economics (HFI), 2020)
We use the entry of 17 external shopping malls in Sweden to investigate how they have affected the performance of incumbent firms located in the city centres of small cities. We find that entry by external shopping malls decreased labour productivity for incumbent firms in city centres by -5.31%. However, when using time-specific fixed effects to control for common time trends in retailing in small cities, the impact on labour productivity, revenues, and number of employees due to the entry of external shopping malls becomes insignificant. The negative impact on incumbent firms is thus not due to the entry of external shopping malls but rather due to long-term negative economic trends in these cities.
Keywords: D22; L25; P25; R12; 330; external shopping malls; city centre; firm performance; agglomeration economies; competition; difference-in-differences